Sytuacja społeczno-gospodarcza jako determinanta migracji wewn\~netrznych w Polsce; Socio-economic situation as the determinant of internal migration in Poland - Justyna Wilk; Michal Bernard Pietrzak; Stanislaw Matusik (Institute of Economic Research (IER), 2013)
– Internal population migration flows constitute an inherent element of the market economy. Under relatively stable political conditions, the nature of internal migration is reflected in economic reasons as a result of the regional socio-economic situation. The subject of this paper was to examine relationships between socio-economic situation and internal migration phenomena in Poland. The investigation covers the period of time after Poland's accession to the EU, with two sub-periods reflect in economic cycle. Inter- and intraregional (NTS-2) migration flows were characterized by a set of migration coefficients. Their implementations were referred to the values of composite measures describing socio-economic situation of Polish regions (NTS-2) and its particular aspects.
Keywords: J11; O11; R11; R23; 330; regional development; internal migration; synthetic measure of development